The many faces of childhood : diversity in development - SHORE Cecilia M. (Boston : Pearson, 2004)
A collection of professional journal articles that represents development from birth through middle childhood years across physical, perceptual-cognitive, and socio-emotional development. These readings represent not only cultural comparisons, but also more specific environments, such as the neighborhood, the family, and endogenous factors
Includes bibliography
Keywords: Child development, Child development Cross-cultural studies, Individual differences